Analisa Risiko Pinjaman Online Ilegal Dalam Praktik Teknologi Finansial - Wahyu Syarvina; Sri Sudiarti (Jurnal Riset Akuntansi dan Bisnis, 2022)
The progress of the Indonesian economy has now entered the digital era 4.0 where many human roles have been replaced with the role of technology and digital. Some fields have an online version, such as e-commerce, online learning, online banking and so on. This digitalization has also entered the financial industry, known as Financial Technology. This study aims to discuss the risks of illegal online loans, of course, very disturbing in society. The research method used is a qualitative research method, the data obtained through observation and in-depth interviews. In the practice of financial technology against illegal online loans, it causes the misuse of data belonging to the borrower's consumer without permission by the platform by accessing data on cellular phone devices. Violations that occur to borrowing consumers for misuse of personal data on cellular networks by companies include intimidating billing, distribution of personal data on contacts on consumer numbers to sexual harassment. The targets of this illegal financial technology are people who have minimal financial knowledge, are in desperate need of money and have a consumptive lifestyle. Various modes are carried out to ensnare potential customers so that those without careful calculations are trapped and bear the risk.